REAKSI PASAR ATAS PANDEMI VIRUS CORONA PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - Nabiell Ghibran; Lukman Effendy; Indria Puspitasari Lenap (Politeknik Ubaya, 2021)
Abstract The study was intended to analyze the reactions of Indonesia's capital markets on events Indonesia tested positive for the corona virus pandemic. The study adopted an 11-day period of event study analysis. The population in this study is the entire company listed on the LQ45 index at the Indonesian stock exchange in February - June 2020. Sampling taken in this study uses an impressive sampling technique. Samples obtained by criteria on this research account number 42 companies. Variables used in this study are abnormal return and trading volume of activity. The study used paired sample t-test analysis methods. The research indicates that there was no significant difference between average abnormal return before and after the Indonesia announcement was positive the corona virus pandemic. This is indicated by the results of the significant paired sample t-test that have a value of 0.924 > 0.05. Additionally, this study indicates that there was no significant difference in average trading volume activity before and after the events of the Indonesian announcement was positive that the corona virus pandemic. This is indicated by the results of the significant paired sample t-test that have a value of 0.936 > 0.05. Keywords : Event Study, Corona Virus Pandemic, Abnormal Return, Trading Volume Activity